Enhancing Customer Relationships: A Case Study of CRM Practices at City Square Mart in Ahmedabad city of Gujarat State - Arima Singh; Rupashree Nandy; Jignesh Vidani (MultiTech Publisher, 2024)
This study paper provides an in-depth examination of customer relationship management (CRM) operations conducted at City Square Mart, a well-known retail business specializing in supermarket trends. This research seeks to provide insights that will improve the development and implementation of CRM strategies in the retail industry by conducting interviews with store managers and analyzing their CRM methods. This study analyzes key elements of consumer engagement channels, such as in-store experiences and online platforms, to understand how City Square Mart effectively combines these channels to provide a seamless and cohesive customer experience. This research also examines consumer feedback methods, loyalty programs, complaint management processes, and initiatives aimed at personalization and customization of goods. The results of this research provide important insights for retail managers who want to improve their CRM strategies and for academics who want to increase their understanding of customer relationship management in the retail industry. This research aims to improve customer interactions and drive company success in the changing retail market by analyzing the unique CRM tactics implemented by City Square Mart